The Ton Motor - Ratliff, Anna C.; Buchanan, Susan K.; Celia, Herve (Frontiers in Microbiology, 2022)
The Ton complex is a molecular motor at the inner membrane of Gram-negative bacteria that uses a proton gradient to apply forces on outer membrane proteins to permit active transport of nutrients into the periplasmic space. Recently, the structure of the ExbB-ExbD subcomplex was determined in several bacterial species, but the complete structure and stoichiometry of TonB has yet to be determined. The C-terminal end of TonB is known to cross the periplasm and interact with TonB-dependent outer membrane transport proteins with high affinity. Yet despite having significant knowledge of these transport proteins, it is not clear how the Ton motor opens a pathway across the outer membrane for nutrient import. Additionally, the mechanism by which energy is harnessed from the inner membrane subcomplex and transduced to the outer membrane via TonB is not well understood. In this review, we will discuss the gaps in the knowledge about the complete structure of the Ton motor complex and the relationship between ion flow used to generate mechanical work at the outer membrane and the nutrient transport process.